2013
DOI: 10.3109/09540261.2013.766154
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatry of corticobasal degeneration and progressive supranuclear palsy

Abstract: Corticobasal syndrome (CBS) and progressive supranuclear palsy syndrome (PSPS) are two of the atypical Parkinsonism syndromes, in that patients exhibit rigidity, occasional tremor and postural instability, but do not symptomatically respond to dopamine replacement. CBS and PSPS can often present with complex cognitive difficulties and neuropsychiatric disturbances. Symptoms of depression, apathy, or agitation can be subtle and are often overlooked as reactions to learning a new diagnosis of Parkinsonism. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…Changes in behavior and personality, similar to those observed in frontotemporal dementia, are common in CBS . Surprisingly, however, very few studies have examined social cognition systematically.…”
Section: Cognition In Cbsmentioning
confidence: 91%
“…Changes in behavior and personality, similar to those observed in frontotemporal dementia, are common in CBS . Surprisingly, however, very few studies have examined social cognition systematically.…”
Section: Cognition In Cbsmentioning
confidence: 91%
“…PSP and corticobasal syndrome (CBS) are common forms of atypical parkinsonism (APS) and, in early stages, can be sometimes quite difficult to diagnose given that they can overlap clinically with PD and other parkinsonian syndromes, including MSA. Previous imaging studies have reported in CBS either asymmetric hypoperfusion or reduced metabolism, mainly in the striatum, as well as parietal and frontal cortex contralateral to the affected limb . CBS may also be variably associated with asymmetric striatal dopamine denervation (e.g., and Cilia and colleagues.…”
Section: Differentiating Atypical Parkinsonisms From Pdmentioning
confidence: 99%
“…CBS may also be variably associated with asymmetric striatal dopamine denervation (e.g., and Cilia and colleagues. Similarly, PSP patients may present with a variable pattern of hypometabolism in the fronto‐striatal‐thalamic regions depending on the clinical presentation and progression . Families with mutations in the progranulin gene presented profound imaging changes of asymmetric hypoperfusion on SPECT and parietal atrophy .…”
Section: Differentiating Atypical Parkinsonisms From Pdmentioning
confidence: 99%
“…Myoclonus, asymmetric dystonia, alien limb phenomenon, frontal executive dysfunction, and visuospatial deficits are secondary criteria. Episodic memory is relatively preserved as hippocampi and temporal cortices are unaffected 26. Patients with PSP or CBD may develop behavioral disturbances similar to bvFTD or PPA.…”
Section: Clinical Subtypesmentioning
confidence: 99%